2012
DOI: 10.1042/bj20120008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and cellular functions of class II phosphoinositide 3-kinases

Abstract: Class II isoforms of PI3K (phosphoinositide 3-kinase) are still the least investigated and characterized of all PI3Ks. In the last few years, an increased interest in these enzymes has improved our understanding of their cellular functions. However, several questions still remain unanswered on their mechanisms of activation, their specific downstream effectors and their contribution to physiological processes and pathological conditions. Emerging evidence suggests that distinct PI3Ks activate different signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
168
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 98 publications
(246 reference statements)
7
168
0
3
Order By: Relevance
“…This is in accordance with previous fi ndings of intact insulin-stimulated PI3k activity in human skeletal muscle ( 12 ). Only a little is known about the function of class II PI3k, although it has been shown that the C2 ␤ subunit, which is encoded by the PIK3C2B gene, is directly activated by growth factors in vitro ( 45 ). It is therefore possible that the confi rmed by incubation of C2C12 cells in this study (32)(33)(34).…”
Section: Discussionsupporting
confidence: 78%
“…This is in accordance with previous fi ndings of intact insulin-stimulated PI3k activity in human skeletal muscle ( 12 ). Only a little is known about the function of class II PI3k, although it has been shown that the C2 ␤ subunit, which is encoded by the PIK3C2B gene, is directly activated by growth factors in vitro ( 45 ). It is therefore possible that the confi rmed by incubation of C2C12 cells in this study (32)(33)(34).…”
Section: Discussionsupporting
confidence: 78%
“…These findings suggest two possible scenarios: (1) that PI(3)P is produced by alternative sources such as the class II PI3Ks (Devereaux et al, 2013;Falasca and Maffucci, 2012;Posor et al, 2013); and/or (2) that a compensatory mechanism independent of PI(3)P is triggered to cope with the loss of Vps34. Previous reports indicate that expression of the constitutively active mutant of Rab5 can bypass the loss of EEA1 membrane localization upon wortmannin treatment Simonsen et al, 1998), and that wortmannin activates Rab5 (Chen and Wang, 2001).…”
Section: ) In Vps34mentioning
confidence: 96%
“…PI(3)P is also known to be generated in the PM. In adipocytes, PI(3)P is generated in the PM upon insulin stimulation and facilitates the translocation of the glucose transporter GLUT4 to the PM (60,61). In HeLa cells, PI(3)P is generated in the PM in response to lysophosphatidic acid and stimulates cell migration (62).…”
Section: Discussionmentioning
confidence: 99%